2015
DOI: 10.1128/jvi.03194-14
|View full text |Cite
|
Sign up to set email alerts
|

The Avian-Origin PB1 Gene Segment Facilitated Replication and Transmissibility of the H3N2/1968 Pandemic Influenza Virus

Abstract: IMPORTANCEDespite the high impact of influenza pandemics on human health, some mechanisms underlying the emergence of pandemic influenza viruses still are poorly understood. Thus, it was unclear why both H2N2/1957 and H3N2/1968 reassortant pandemic viruses contained, in addition to the avian HA, the PB1 gene segment of the avian parent. Here, we addressed this long-standing question by modeling the emergence of the H3N2/1968 virus from its putative human and avian precursors. We show that the avian PB1 segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Recently, Wendel et al (2015) demonstrated that the viral polymerase activity of a seasonal H2N2 vRNP can be enhanced by replacing its PB1 with an HK/68 PB1. Our findings also support this, but our results further suggest that there are some mutations in the PB2 of the HK/68 virus that also might contribute to the enhanced viral polymerase activity of pandemic H3N2 virus (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wendel et al (2015) demonstrated that the viral polymerase activity of a seasonal H2N2 vRNP can be enhanced by replacing its PB1 with an HK/68 PB1. Our findings also support this, but our results further suggest that there are some mutations in the PB2 of the HK/68 virus that also might contribute to the enhanced viral polymerase activity of pandemic H3N2 virus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both 1957 and 1968 pandemic viruses had an avian PB1 segment, whereas the 2009 pandemic virus had avian PB2 and PA gene segments circulating in swine influenza viruses (Kawaoka et al, 1989;Smith et al, 2009;Webby et al, 2000). Although there is some evidence suggesting that reassorted polymerase complexes with avian PB1 might have enhanced polymerase activity in human cells (Chen et al, 2008;Li et al, 2009;Naffakh et al, 2000;Wendel et al, 2015), the evolutionary advantages of having a reassorted polymerase complex in a pandemic virus are not clear. For example, it is not known whether a reassorted polymerase might have a role in facilitating the genesis or transmission of pandemic influenza virus.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reassortment between a human H3N2 and an avian H5N1 virus led to the generation of an avian PB1-containing reassortant with increased virulence in vivo, although the reassorted polymerase activity remained unchanged in vitro [15]. Swapping the PB1 segment of a human seasonal H2N2 virus with that of the 1968 pandemic strain, which is of avian-origin, increased viral polymerase activity and facilitated replication and transmission of the reassortant virus in guinea pigs [16].The 2009 pandemic H1N1 (pH1N1) is a "quadruple reassortant" virus resulted from the reassortment between the "triple reassortant" North American swine H1N2 viruses and the Eurasian "avian-like" swine H1N1 viruses. It contains the PB2 and PA gene segments of avian-origin, and the PB1 segment originated from human seasonal H3N2 viruses.…”
mentioning
confidence: 99%
“…Notably, a recent study revealed that the avian-origin PB1 segment that represents the ancestor of the PB1 of the pandemic 2009 H1N1 influenza virus further facilitated the transmission and replication of the pandemic human H3N2 influenza virus in 1968 (Wendel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%